PENGARUH PROPORSI LIMBAH DAUN DAN JENIS MOL TERHADAP MUTU BOKASI - Irfan Irfan; Dewi Yunita; Ismail Sulaiman; Muhammad Ikhsan Sulaiman; Fathur Rizky Maulana (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2022)
[EFFECT OF LEAF WASTE PROPORTION AND TYPES OF LOCAL MIKROORGANISM ON THE QUALITY OF BOKASHI]. The purpose of this study was to get a combination of the treatment of the leaf waste proportion and local microorganism (MOL) type to the quality of bokashi. The use of specific MOL as a bioactivator is expected to produce a good bokashi. The production of bokashi was conducted at the Garbage Collection Center of Syiah Kuala University, Banda Aceh, Indonesia. The experimental design was a completely randomized design (CRD) with 2 factors including the proportion of leaves (D) and the type of MOL (M). The first factor consisted of two levels (50% and 70% leaf) and the second factor consisted of 4 levels (rice MOL, soil MOL, bokashi MOL, and leaf waste MOL). The quality of bokashi was measured based on the total cell counts of microbes, pH, C/N ratio, descriptive test (texture, aroma, and colour), and plant growth tests on corn. The results showed that all bokashi have complied with SNI 19-7030- 2004. The best bokasi was obtained from the combination between 50% leaf waste proportion and MOL type of rice. This bokashi had a total microbes of 4.1 x 108 CFU/g, pH value of 7.4, C/N ratio of 10.2, with organoleptic characteristics of loose texture and slightly moisture, slightly soil-scented, blackish color and the hight of test plant of 61 cm. The main advantage of this bokashi compared to others was in the highest number of microbes total and the best texture.